Two decades of research capacity strengthening and reciprocal learning on sexual and reproductive health in East Africa - a point of (no) return - Caroline Frisendahl; Emelie Looft-Trägårdh; Amanda Cleeve; Susan Atuhairwe; Elin C. Larsson; Othman Kakaire; Herbert Kayiga; Annette Aronsson; Anne Kihara; Marleen Temmerman; Marie Klingberg Allvin; Josaphat Byamugisha; et al. (Taylor & Francis Group, 2024)
As the world is facing challenges such as pandemics, climate change, conflicts, and changing political landscapes, the need to secure access to safe and high-quality abortion care is more urgent than ever. On 27th of June 2023, the Swedish government decided to cut funding resources available for developmental research, which has played a fundamental role in the advancement of sexual and reproductive health and rights (SRHR) globally, including abortion care. Withdrawal of this funding not only threatens the fulfilment of the United Nations sustainable development goals (SDGS) - target 3.7 on ensuring universal access to SRHR and target 5 on gender equality - but also jeopardises two decades of research capacity strengthening. In this article, we describe how the partnerships that we have built over the course of two decades have amounted to numerous publications, doctoral graduates, and important advancements within the field of SRHR in East Africa and beyond.